Packaging film and packaging material

By adopting a laminated structure in the polyester film, polyester resin containing diol residues and dicarboxylic acid residues and vinyl alcohol-based copolymer resins are alternately stacked to form a multilayer film, solving the problem of high oxygen permeability of the polyester film, achieving the effect of low oxygen permeability and low moisture permeability, while improving optical performance and printing suitability.

CN119795723APending Publication Date: 2025-04-11MIKEVO GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411394886.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-10
Filing Date
2024-10-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Polyester films have high oxygen permeability and are difficult to apply in areas where oxygen barriers are required.

Method used

A laminated structure is adopted, in which the first layer contains a polyester resin containing a diol residue and a dicarboxylic acid residue, and the second layer is a vinyl alcohol-based copolymer resin. Multi-layer films are formed by alternate stacking to reduce oxygen permeability.

Benefits of technology

The oxygen permeability at 23°C is achieved at 10 cc/(m2·day·atm) or less, and the moisture permeability is 50 g/(m2·day) or less, and has good optical properties and printing suitability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795723A_ABST
    Figure CN119795723A_ABST
Patent Text Reader

Abstract

A packaging film and a packaging material for packaging food and the like are disclosed. A packaging film according to an embodiment includes a laminate including a first layer including a polyester resin containing a diol residue and a dicarboxylic acid residue, and a second layer disposed on the first layer, the second layer including a vinyl alcohol-based copolymer resin, the packaging film has an oxygen permeability of 10 cc / (m2 * day * atm) or less at 23 DEG C. The present embodiment can provide a packaging film and a packaging material having excellent characteristics such as oxygen permeability and moisture permeability, good optical properties, and improved printability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present embodiment relates to a packaging film and a packaging material which have excellent oxygen permeability characteristics and the like and can be effectively used for packaging food and the like. Background Art

[0002] Products in various industrial fields require films that can block oxygen or moisture. For example, there are food packaging materials where freshness is important and packaging materials for electronic parts that are sensitive to oxygen. In particular, there is an increasing demand for films that have low oxygen permeability while having appropriate heat resistance, mechanical strength and transparency.

[0003] Polyester has stable properties in terms of heat resistance, mechanical strength, and transparency. Therefore, polyester is widely used in many fields such as containers, packaging materials, films, cables, etc.

[0004] However, since polyester has a high oxygen permeability, there is a problem that it is difficult to apply it to fields that require oxygen barrier.

[0005] The above-mentioned background technology is the technical information possessed by the inventor to derive the present invention or the technical information mastered in the process of deriving the present invention, and therefore cannot be regarded as the known technology disclosed to the public before applying for the present invention.

[0006] Relevant prior arts include Korean authorized patent No. 10-0516550, etc. Summary of the invention

[0007] Technical issues

[0008] An object of the present embodiment is to provide a packaging film or the like having excellent oxygen permeability characteristics and the like.

[0009] Solutions to the problem

[0010] In order to achieve the above object, a packaging film according to one embodiment includes a laminate including a first layer and a second layer arranged on the first layer, wherein the first layer includes a polyester resin containing a diol residue and a dicarboxylic acid residue, and the second layer includes a vinyl alcohol-based copolymer resin.

[0011] The packaging film may have a 10cc / (m 2 ·day·atm) or less oxygen permeability.

[0012] The packaging film may have a thickness of 50 g / (m 2 · days) or less.

[0013] The vinyl alcohol-based copolymer resin may be a butene glycol-vinyl alcohol copolymer resin or an ethylene-vinyl alcohol copolymer resin.

[0014] The thermal decomposition temperature of the vinyl alcohol-based copolymer resin may be 210°C to 230°C.

[0015] The first layer may be located on at least one of the outermost layers on both sides of the laminate.

[0016] The laminate may have a light transmittance of 80% or more in a visible light region having a wavelength of 380 nm to 780 nm.

[0017] The haze of the laminate may be 30% or less.

[0018] The stacked body may be formed by alternately stacking the first layer and the second layer in 3 to 225 layers.

[0019] The maximum thickness deviation (MTD) is expressed by the following formula 2: 200 ) can be less than 10 μm.

[0020] [Formula 2]

[0021] MTD 200 =THK max -THK min

[0022] In the above formula 1, THK max It refers to the maximum thickness when the thickness of a packaging film sample with a minimum width of 200 cm is measured every 2 cm. min It refers to the minimum thickness when the thickness of a packaging film sample with a width of 200 cm is measured every 2 cm.

[0023] In order to achieve the above object, a packaging material according to one embodiment includes the packaging film as described above.

[0024] Effects of the Invention

[0025] The present embodiment can provide a packaging film or the like having excellent oxygen permeability characteristics and the like.

[0026] In addition, the present embodiment can provide a packaging film and a packaging material having excellent properties such as oxygen permeability and moisture permeability, good optical properties, and improved printability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram for explaining a laminated body included in a packaging film according to one embodiment.

[0028] Figure 2 It is a schematic diagram for explaining a laminated body included in a packaging film according to another embodiment.

[0029] Figure 3The diagram is a schematic diagram for explaining a laminate included in a packaging film according to still another embodiment.

[0030] Description of Reference Numerals

[0031] 100: Packaging film

[0032] 10: Laminated body

[0033] 11: First floor

[0034] 12: Second layer DETAILED DESCRIPTION

[0035] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that a person skilled in the art can easily implement the present invention. However, the present invention can be implemented in a variety of different embodiments and is not limited to the embodiments described in this specification. Throughout the specification, the same reference numerals are given to the same or similar components.

[0036] Throughout this specification, the term "combination of..." included in the Markush-type description refers to a mixture or combination of one or more constituent elements selected from the group consisting of the constituent elements of the Markush-type description, thereby meaning that the present invention includes one or more constituent elements selected from the group consisting of the above constituent elements.

[0037] Throughout the present specification, descriptions in the form of "A and / or B" mean "A, B, or A and B".

[0038] Throughout this specification, unless otherwise specified, terms such as "first", "second", etc. are used to distinguish the same terms from each other. In addition, unless otherwise specified, descriptions indicating the singular should be understood to include the plural.

[0039] Throughout the specification, when a component is referred to as “comprising” an element, instead of excluding any other elements, it may mean that the component may further include other elements unless expressly specified otherwise.

[0040] Throughout this specification, "B is on A" means that B is directly in contact with A or B is on A with another layer in between, and should not be limited to the meaning that B is in contact with the surface of A.

[0041] In this specification, the drawings may be shown in an exaggerated or omitted manner for the purpose of explanation, but this should not be interpreted as limiting the scope of the present embodiment.

[0042] A multilayer film in which a layer having an oxygen barrier function is inserted into a layer containing a polyester resin is proposed as a packaging film. The inventors propose a packaging film formed by laminating a first layer containing a polyester resin and a second layer having an oxygen barrier function. The film has not only excellent mechanical and optical properties, but also excellent oxygen and moisture barrier properties, improved processability, and the polyester resin can be recycled, so it has excellent application value as a packaging film.

[0043] Figure 1 A schematic diagram for explaining a laminate included in a packaging film according to an embodiment. Figure 2 A schematic diagram for explaining a laminate included in a packaging film according to another embodiment. Figure 3 This is a schematic diagram for explaining a laminated body included in a packaging film according to still another embodiment. Hereinafter, this embodiment will be described in more detail with reference to the above-mentioned drawings.

[0044] Laminated body

[0045] In one or more embodiments, the laminate 10 is a laminate 10 in which a first layer 11 and a second layer 12 including polymer resins distinguished from each other are laminated.

[0046] The first layer 11 and the second layer 12 may be stacked one above the other. The first layer 11 and the second layer 12 may be stacked alternately in three layers or four layers or more.

[0047] In one or more embodiments, the first layer 11 includes a copolyester resin.

[0048] The copolyester resin may be obtained by polymerizing a diol containing two or more diol residues and one or more dicarboxylic acid residues and a dicarboxylic acid.

[0049] The copolyester resin may be obtained by polymerizing a diol containing three or more diol residues and one or more dicarboxylic acid residues and a dicarboxylic acid.

[0050] The diol residue may include an aliphatic diol residue, an alicyclic diol residue, an aromatic diol residue or a derivative thereof. For example, the aliphatic diol residue may be an aliphatic diol residue having 2 to 10 carbon atoms and may have a linear or branched structure.

[0051] Specific examples of the aliphatic diol including the above aliphatic diol residue may include ethylene glycol, diethylene glycol, neopentyl glycol, 1,3-propylene glycol, 1,2-octanediol, 1,3-octanediol, 2,3-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,2-diethyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 3-methyl-2-ol 1,5-pentanediol, 1,1-dimethyl-1,5-pentanediol, 1,6-hexanediol, 2-ethyl-3-methyl-1,5-hexanediol, 2-ethyl-3-ethyl-1,5-hexanediol, 1,7-heptanediol, 2-ethyl-3-methyl-1,5-heptanediol, 2-ethyl-3-ethyl-1,6-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, derivatives thereof, or any combination thereof.

[0052] The above-mentioned dicarboxylic acid residue may include an aromatic dicarboxylic acid residue, an aliphatic dicarboxylic acid residue, an alicyclic dicarboxylic acid residue or an esterified residue thereof.

[0053] Specific examples of the dicarboxylic acid including the above-mentioned dicarboxylic acid residue may include terephthalic acid, dimethyl terephthalate, isophthalic acid, naphthalene dicarboxylic acid, phthalic acid, adipic acid, azelaic acid, sebacic acid, sebacic acid and esters thereof; or combinations thereof. Specifically, the above-mentioned dicarboxylic acid may include at least one selected from the group consisting of terephthalic acid, dimethyl terephthalate, naphthalene dicarboxylic acid and phthalic acid.

[0054] In one or more embodiments, the copolyester resin may be polymerized from a diol including two or more diol residues and at least one aromatic dicarboxylic acid residue and an aromatic dicarboxylic acid.

[0055] In one or more embodiments, the copolyester resin may be polymerized from a diol including ethylene glycol and one or more comonomers; and one or more aromatic dicarboxylic acids. According to another embodiment, the copolyester resin may be polymerized from a diol including ethylene glycol and two or more comonomers; and an aromatic dicarboxylic acid.

[0056] The above-mentioned diol residue may include ethylene glycol residue. Based on the above-mentioned diol as a whole, the above-mentioned diol may include 50 mol % to 90 mol % of ethylene glycol. Based on the above-mentioned diol as a whole, the above-mentioned diol may include 60 mol % to 90 mol %, 63 mol % to 85 mol % or 65 mol % to 83 mol % of ethylene glycol. When the above range is met, the above-mentioned polyester resin may have an improved thermal shrinkage and a reduced agglomeration rate.

[0057] The above-mentioned diol can include the remaining diols other than ethylene glycol in the diols cited above as comonomers. For example, the above-mentioned diol can include diethylene glycol, 1,4-cyclohexanedimethanol, 1,3-propylene glycol, 1,2-octanediol, 1,3-octanediol, 2,3-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propylene glycol, 2,2-diethyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,1-dimethyl-1,5-pentanediol or a combination thereof as comonomers. Specifically, the above-mentioned diol can include at least one selected from the group consisting of neopentyl glycol, cyclohexanedimethanol and diethylene glycol as a comonomer.

[0058] In one or more embodiments, the above-mentioned glycol may include diethylene glycol as a comonomer. Based on the above-mentioned glycol as a whole, the content of diethylene glycol in the above-mentioned glycol may be 1 mol % to 15 mol %. Specifically, based on the above-mentioned glycol as a whole, the content of diethylene glycol in the above-mentioned glycol may be 1 mol % to 10 mol %, 1 mol % to 5 mol %, 5 mol % to 10 mol % or 3 mol % to 7 mol %. When the above range is met, the above-mentioned polyester resin may have an improved thermal shrinkage and a reduced agglomeration rate.

[0059] In one or more embodiments, the above-mentioned diol may include at least one of neopentyl glycol and cyclohexanedimethanol as a comonomer. Based on the above-mentioned diol as a whole, the content of neopentyl glycol and / or cyclohexanedimethanol in the above-mentioned diol can be more than 1 mol%, more than 5 mol%, more than 10 mol%, more than 15 mol% or more than 20 mol%. Based on the above-mentioned diol as a whole, the content of neopentyl glycol and / or cyclohexanedimethanol in the above-mentioned diol can be less than 50 mol%, less than 45 mol%, less than 40 mol%, less than 35 mol%, less than 30 mol% or less than 25 mol%.

[0060] When the above range is satisfied, the copolyester resin can help obtain a suitable heat shrinkage rate in a direction perpendicular to the main shrinkage direction during stretching. If the content of the neopentyl glycol and / or cyclohexanedimethanol exceeds the above range, the copolyester resin may wrinkle or deform during stretching. In addition, when the content of the neopentyl glycol and / or cyclohexanedimethanol is less than the above range, the amorphous region of the copolyester resin will expand, so the shrinkage characteristics in the main shrinkage direction can be improved, but the shrinkage characteristics in the direction perpendicular to the main shrinkage direction will deteriorate, resulting in an increase in the expansion coefficient.

[0061] In one or more embodiments, the diol may include at least one selected from neopentyl glycol and cyclohexanedimethanol; and diethylene glycol as a comonomer. For example, the diol may include 20 mol % to 30 mol % of at least one selected from neopentyl glycol and cyclohexanedimethanol; and 1 mol % to 15 mol % of diethylene glycol as a comonomer.

[0062] In one or more embodiments, based on the above-mentioned dicarboxylic acid as a whole, the above-mentioned dicarboxylic acid may contain terephthalic acid or dimethyl terephthalate at 80 mol %, 90 mol % or 95 mol %. However, the above-mentioned dicarboxylic acid may not include isophthalic acid. For example, the content of isophthalic acid in the above-mentioned dicarboxylic acid may be less than 5 mol %, less than 3 mol % or less than 1 mol %.

[0063] In one or more embodiments, the diol includes 20 mol % to 40 mol % of at least one selected from the group consisting of neopentyl glycol, cyclohexanedimethanol, diethylene glycol and a combination thereof as a comonomer, and the content of isophthalic acid in the aromatic dicarboxylic acid may be less than 1 mol %. As a specific embodiment, the copolyester resin may be ethylene glycol-modified polyethylene terephthalate (PETG).

[0064] In one or more embodiments, the copolyester resin may further include an alcohol other than the diol, such as a monohydric alcohol. For example, the monohydric alcohol may be methanol, ethanol, isopropanol, allyl alcohol, or benzyl alcohol. Specifically, based on 100 parts by weight of the diol, the copolyester resin may include 10 to 40 parts by weight or 15 to 30 parts by weight of the monohydric alcohol.

[0065] In one or more embodiments, the melting point of the copolyester resin may be 170° C. to 230° C. Specifically, the melting point of the copolyester resin may be 180° C. to 220° C., or 190° C. to 210° C. When the above range is met, since the melting point of the first layer 11 resin is lower than or equal to the thermal decomposition temperature of the second layer 12 resin, the coextrusion process can be further effectively applied.

[0066] In one or more embodiments, the second layer 12 includes a vinyl alcohol-based copolymer resin. By using a vinyl alcohol-based copolymer resin in the second layer 12, the oxygen permeability of the laminate 10 can be further improved.

[0067] The vinyl alcohol-based copolymer resin may include butenediolvinyl alcohol copolymer resin (BVOH) or ethylene glycol-vinyl alcohol copolymer resin (EVOH).

[0068] The above-mentioned ethylene glycol-vinyl alcohol copolymer resin (EVOH) is a copolymer of ethylene and vinyl alcohol, and its commercially available products include Soarnol of Mitsubishi Chemical Corporation, EVAL of Kuraray Corporation, etc. The vinyl content of the above-mentioned ethylene glycol-vinyl alcohol copolymer resin can be more than 20 mol%, more than 25 mol%, more than 30 mol%, more than 35 mol% or more than 40 mol%. The content of the above-mentioned vinyl can be less than 48 mol% or less than 45 mol%. When having the above-mentioned vinyl content, the ratio of the repeating unit of the vinyl alcohol group and the vinyl group is adjusted to a suitable range, thereby being helpful in controlling the moisture permeability and oxygen permeability of the packaging film at the same time.

[0069] The above-mentioned butenediol-vinyl alcohol copolymer (BVOH) can be produced by hydrolyzing vinyl acetate after copolymerization of butenediol and vinyl acetate. Alternatively, NICHIGOG-POLYMER, which is a commercially available product sold by Mitsubishi Chemical Corporation, can be used. TM BVOH. Specifically, as NICHIGO G-POLYMER TM The granular product may be any one selected from the group consisting of AVE8077P, BVE8049P, OKS-8074P, OKS-8211P and a combination thereof.

[0070] In one or more embodiments, the butene glycol-vinyl alcohol copolymer (BVOH) is preferably used as the second layer 12 resin compared to the ethylene glycol-vinyl alcohol copolymer resin (EVOH). This means that the butene glycol-vinyl alcohol copolymer (BVOH) has very excellent interlayer adhesion compared to the ethylene glycol-vinyl alcohol copolymer resin (EVOH), and can be manufactured to have excellent adhesion with the polyester resin as the first layer 11 resin even without forming a separate adhesive layer.

[0071] The second layer 12 may be a water-soluble layer that dissolves in water. In particular, the second layer 12 resin may be soluble not only in high temperature water but also in relatively low temperature water. Specifically, the second layer 12 resin may be substantially completely soluble in 90°C water within 1 hour, substantially completely soluble in 70°C water within 1 hour, and substantially completely soluble in 20°C water within 2 hours. The second layer 12 resin has high solubility in water, and therefore, as described later, the water separability of the laminate 10 may be improved. In addition, the second layer 12 resin is highly soluble in water, and therefore, when the laminate 10 is recycled, substantially no residual composition will be left on the first layer 11.

[0072] The above-mentioned second layer 12 resin may have a melt flow rate (MFR) of more than 10 g / 10 min at 210° C. Specifically, the melt flow rate (MFR) of the above-mentioned second layer 12 resin may be more than 15 g / 10 min, more than 20 g / 10 min, more than 25 g / 10 min, or more than 30 g / 10 min. The melt flow rate (MFR) of the above-mentioned second layer 12 resin may be less than 100 g / 10 min. When the above-mentioned range is met, the manufacturing processability of the second layer 12 can be improved. Exemplarily, the second layer 12 can be easily formed by a co-extrusion process.

[0073] The viscosity of the second layer 12 resin may be 30,000 Poise or less at 230°C. Specifically, the viscosity of the second layer 12 resin may be 20,000 Poise or more, 10,000 Poise or more, or 9,000 or less at 230°C. The viscosity of the second layer 12 resin may be 100 Poise or more at 230°C. Specifically, the viscosity of the second layer 12 resin may be 300 Poise or more, 500 Poise or more, or 1,000 Poise or more at 230°C. When the above range is met, the fluidity of the second layer 12 resin during extrusion can be ensured, so that it can be easily formed by a co-extrusion process.

[0074] The thermal decomposition temperature of the above-mentioned second layer 12 resin may be 210°C to 230°C. Specifically, the thermal decomposition temperature of the above-mentioned second layer 12 resin may be 215°C to 225°C, or may be 217°C to 223°C. As a general polyester, polyethylene terephthalate (PET) has a higher melting point than the thermal decomposition temperature of the polyvinyl alcohol (PVOH)-based resin, and therefore it is difficult to apply the co-extrusion process. In the case of the present embodiment, the melting point of the above-mentioned first layer 11 resin may be less than or equal to the thermal decomposition temperature of the above-mentioned second layer 12 resin. Therefore, the first layer 11 and the second layer 12 of the present embodiment may be easily applicable to the co-extrusion process.

[0075] The glass transition temperature of the resin of the second layer 12 may be above 60°C. Specifically, the glass transition temperature of the resin of the second layer 12 may be above 65°C, above 70°C, or above 75°C. The glass transition temperature of the resin of the second layer 12 may be below 200°C, below 150°C, or below 100°C. Generally, a high temperature environment may be formed inside a display device, so a heat-resistant material is required. When the above range is met, the heat resistance of the second layer 12 can be enhanced.

[0076] In one or more embodiments, a separate adhesive layer may be included between the first layer 11 and the second layer 12. Alternatively, the first layer 11 and the second layer 12 may be in direct contact without a separate adhesive layer therebetween.

[0077] When a butene glycol-vinyl alcohol copolymer resin (BVOH) is used as the resin of the second layer 12, even if the first layer 11 and the second layer 12 are in direct contact, the first layer 11 and the second layer 12 have high adhesion and are substantially not peeled off in a high temperature and humid environment. It has been confirmed that even if the laminate 10 is exposed to a constant temperature and humidity chamber (QM200M of QMESYS) for more than 500 hours at a temperature of 85°C and a relative humidity of 85%, there is no peeling phenomenon between the first layer 11 and the second layer 12. Therefore, the packaging film can omit the interlayer adhesive layer, simplify the process, and provide a film having excellent physical properties even at a thinner thickness.

[0078] The laminate 10 may include a first layer 11 and a second layer 12 at a certain weight ratio. The content of the second layer 12 may be 1 to 50 parts by weight based on 100 parts by weight of the laminate. The laminate 10 may include 3 to 40 parts by weight or 5 to 30 parts by weight of the second layer 12 based on 100 parts by weight of the laminate.

[0079] The laminate 10 has excellent water-separability, which helps to facilitate the recycling of products using different materials at the same time.

[0080] In one or more embodiments, the second layer 12 is dissolved in water by placing 10 sheets of 1 cm wide and 1 cm long laminate samples at 60±5° C. (i.e., 55° C. to 65° C.) using the laminate 10 and stirring the laminate at 300 rpm for 120 minutes using a stirrer. In this case, the first layer 11 does not dissolve, and can be easily separated, recovered, and reused.

[0081] In one or more embodiments, the second layer 12 can be dissolved in the 1 wt % sodium hydroxide aqueous solution by placing 10 sheets of the laminated body samples having a width of 0.5 cm and a length of 0.25 cm in 85±5° C. (i.e., 80° C. to 90° C.) and stirring at 300 rpm for 15 minutes using a stirrer, so that the second layer 12 can be dissolved in the 1 wt % sodium hydroxide aqueous solution. In this case, the first layer 11 will not dissolve, so that it can be easily separated, recovered, and reused.

[0082] The laminate 10 may have a 2 ·day·atm) or less oxygen permeability.

[0083] The oxygen permeability of the laminate 10 can be 7.5 cc / (m 2 ·day·atm) or less, 5.5cc / (m 2 ·day·atm) or less, 4cc / (m 2 ·day·atm) or less, 3cc / (m 2 ·day·atm) or less, 2cc / (m 2 ·day·atm) or less, 1cc / (m 2 ·day·atm) or less or 0.1cc / (m 2 ·day·atm) or less. Alternatively, it can be 0.05cc / (m 2 The oxygen permeability of the laminate 10 may be 0.0001 cc / m 2 ·day·atm or more. When the above range is satisfied, the laminate 10 can effectively block oxygen flowing in from the outside. The above oxygen permeability is based on measurement at 23°C (±0.5°C).

[0084] The moisture permeability can be evaluated at a temperature of 37.8°C ± 0.5°C and a humidity of 100% RH.

[0085] The moisture permeability of the laminate 10 can be 50 g / (m 2 · days) or less.

[0086] The moisture permeability of the laminate 10 can be 50 g / (m 2 ·day) or less, 45g / (m 2 ·day) or less, 40g / (m 2 ·day) or less, 36g / (m 2 ·day) or less, 25g / (m 2 ·day) or less, 24g / (m 2 ·day) or less than 23g / (m 2 The moisture permeability of the laminate 10 may be 0.0001 g / (m 2·day) or more or 0.001g / (m 2 In this case, the laminate 10 can effectively block moisture flowing in from the outside.

[0087] The moisture permeability of the embodiment described below is the result of measurement at a certain thickness selected from 0.3 mm to 0.15 mm by using a PERMATRAN-W700 tester of MOCON Company of the United States, according to ASTM F1249-20 standard, under the temperature and humidity conditions of 37.8±0.5°C and 100RH%, but the measurement method of the moisture permeability is not limited to this.

[0088] The total number of layers of the laminate 10 may be 4 or more, 6 or more, 10 or more, 31 or more, 35 or more, or 37 or more. The total number of layers of the laminate 10 may be 425 or less, 325 or less, or 225 or less.

[0089] As the total number of layers of the above-mentioned stacked body 10, when it is difficult to distinguish the first layer 11 of the stacked body 10 from the adjacent surface layer because the resin of the surface layer to be described below is the same as the resin of the first layer 11, the number of layers determined assuming the existence of the first layer 11 of the stacked body 10 is used as a basis.

[0090] The laminate 10 is formed by alternately laminating the first layer 11 and the second layer 12 in a multi-layer structure, so that a packaging film having the mechanical strength of the polyester film maintained at an appropriate level or higher can be provided.

[0091] The laminate 10 may be a laminate in which the first layer 11 and the second layer 12 are alternately laminated in 3 or more layers or in a range of 3 to 255 layers. In this case, even if a relatively large amount of the second layer composition is used, the manufacturing processability can be further improved.

[0092] The first layer 11 prevents the second layer 12 from being directly exposed to the external environment, thereby preventing the physical properties of the laminate or the multilayer film from being deteriorated.

[0093] surface layer

[0094] The packaging film of this embodiment may further include a surface layer.

[0095] The surface layer may be disposed on one side or the other side of the laminate 10 .

[0096] The surface layer may be disposed on one side or the other side of the laminate 10. In this case, the laminate 10 may be prevented from being directly exposed to the external environment, thereby preventing the physical properties from being deteriorated.

[0097] The resin of the first layer 11 can be applied to the surface layer. In this case, the mechanical and optical properties and processability of the packaging film can be further improved.

[0098] The thickness of the surface layer may be applied at a thickness ratio of 5 to 30 based on the thickness 100 of the laminate 10. Specifically, the thickness of the surface layer may be applied at a thickness ratio of 10 to 25 or 15 to 20 based on the thickness 100 of the laminate 10.

[0099] If the above-mentioned surface layer is applied to both the upper part and the lower part of the laminate 10 , the thickness of the above-mentioned surface layer means the thickness of one surface layer.

[0100] Packaging film

[0101] The packaging film 100 can have a thermal conductivity of 10 cc / (m 2 ·day·atm) or less oxygen permeability.

[0102] Specifically, the oxygen permeability of the packaging film 100 may be 7.5 cc / (m 2 ·day·atm) or less, 5.5cc / (m 2 ·day·atm) or less, 4cc / (m 2 ·day·atm) or less, 3cc / (m 2 ·day·atm) or less, 2cc / (m 2 ·day·atm) or less, 1cc / (m 2 ·day·atm) or less or 0.1cc / (m 2 ·day·atm) or less. Alternatively, it can be 0.05cc / (m 2 The oxygen permeability of the packaging film 100 may be 0.0001 cc / m 2 ·day·atm or more. When the above range is satisfied, the packaging film 100 can effectively block oxygen flowing in from the outside. The above oxygen permeability is based on measurement at 23°C (±0.5°C).

[0103] The moisture permeability of the packaging film 100 can be 50 g / (m 2 · days) or less.

[0104] The moisture permeability of the packaging film 100 can be 50 g / (m 2 ·day) or less, 45g / (m 2 ·day) or less, 40g / (m 2 ·day) or less, 36g / (m 2 ·day) or less, 25g / (m 2 ·day) or less, 24g / (m 2·day) or less than 23g / (m 2 The moisture permeability of the packaging film 100 may be 0.0001 g / (m 2 ·day) or more or 0.001g / (m 2 In this case, the packaging film 100 can effectively block moisture flowing in from the outside.

[0105] The above-mentioned moisture permeability is measured at a thickness selected from 0.3 mm to 0.15 mm by using a PERMATRAN-W700 tester of MOCON Company of the United States, according to ASTM F1249-20 standard, under temperature and humidity conditions of 37.8±0.5°C and 100RH%, but the measurement method of moisture permeability is not limited to this.

[0106] The packaging film 100 may have a total thickness of 10 μm to 1,000 μm. Specifically, the packaging film 100 may have a total thickness of 20 μm to 500 μm, 30 μm to 250 μm, 40 μm to 200 μm, or 60 μm to 100 μm. The packaging film 100 may omit the adhesive layer between the first layer 11 and the second layer 12, so the overall thickness may be easily adjusted.

[0107] The maximum thickness deviation (MTD) of the packaging film 100 is expressed by the following formula 1: 50 ) may be less than 10 μm. Specifically, the maximum thickness deviation (MTD) of the packaging film 100 is expressed by the following formula 1: 50 ) may be 10 μm or less, 8.5 μm or less, 5 μm or less, 3 μm or less, 2.7 μm or less, 2.5 μm or less, or 2.0 μm or less. When the above range is met, the flatness of the packaging film 100 is easily maintained, thereby improving the manufacturing processability.

[0108] [Formula 1]

[0109] MTD 50 =THK max -THK min

[0110] In the above formula 1, THK max It refers to the maximum thickness when the thickness of the packaging film 100 with a minimum width of 50 cm is measured every 2 cm. min It refers to the minimum thickness when the thickness of the packaging film 100 having a width of 50 cm is measured at intervals of 2 cm.

[0111] The maximum thickness deviation (MTD) of the packaging film 100 is expressed by the following formula 2: 200) may be less than 10 μm. Specifically, the maximum thickness deviation (MTD) of the packaging film 100 is expressed by the following formula 2: 200 ) may be 10 μm or less, 8.5 μm or less, 5 μm or less, 3 μm or less, 2.7 μm or less, 2.5 μm or less, or 2.0 μm or less. When the above range is met, the flatness of the packaging film 100 is easily maintained, thereby improving processability.

[0112] [Formula 2]

[0113] MTD 200 =THK max -THK min

[0114] In the above formula 2, THK max It refers to the maximum thickness when the thickness of a packaging film sample with a minimum width of 200 cm is measured every 2 cm. min It refers to the minimum thickness when the thickness of a packaging film sample with a width of 200 cm is measured every 2 cm.

[0115] The packaging film 100 may have a light transmittance of 80% or more in the visible light region with a wavelength of 380nm to 780nm. Specifically, the light transmittance in the visible light region with a wavelength of 380nm to 780nm may be 85% or more, 90% or more, or 95% or more. The packaging film 100 may have a light transmittance of less than 100% in the visible light region with a wavelength of 380nm to 780nm. When the above range is met, the packaging film 100 has excellent light transmittance, so that when applied to the display device described below, excellent optical performance can be achieved.

[0116] The haze of the packaging film 100 may be 30% or less. Specifically, the haze of the packaging film 100 may be 15% or less, 10% or less, 9% or less, or 5% or less. The haze of the packaging film 100 may be 0.001% or more. When the above range is met, the transparency of the film can be ensured, so that the film can be used for applications requiring light transmittance, and when it is applied to a printed layer, it can be more conducive to production.

[0117] Method for preparing packaging film

[0118] A method for preparing a packaging film 100 according to another embodiment includes: a step of preparing a composition, a step of obtaining an unstretched sheet; and a step of obtaining a multilayer film.

[0119] The step of preparing the composition is a step of preparing the first layer composition and the second layer composition.

[0120] The first layer composition includes a polyester resin containing a diol residue and a dicarboxylic acid residue.

[0121] The second layer composition includes a vinyl alcohol-based copolymer resin.

[0122] Since the specific description about the above-mentioned first layer composition and the second layer composition overlaps with the above description, the detailed description thereof will be omitted.

[0123] The first layer composition and the second layer composition may be prepared in the form of chips. When each composition is prepared in the form of chips, it is easy to store and can also be easily applied to the melting step.

[0124] The preparation step may further include a drying process of drying the first layer composition and the second layer composition in the shape of chips, respectively. The second layer composition may be directly applied to dry packaging.

[0125] The drying may be performed at 40°C to 100°C, or at 50°C to 80°C. The drying may be performed for 2 hours to 24 hours, or for 6 hours to 18 hours. Exemplarily, the drying may be performed by hot air drying. The moisture content in the dried fragments may be 300 ppm or less or 200 ppm or less. The moisture content may be 30 ppm or more. When the fragments are dried to remove moisture as described above, bubbles generated by moisture may be substantially suppressed, and the appearance of the manufactured product may be improved. In addition, smooth processability may be imparted.

[0126] The step of obtaining an unstretched sheet is a step of melt-extruding the first layer composition and the second layer composition, respectively, to obtain an unstretched sheet including a laminated body in which first layers 11 comprising the first layer composition and second layers 12 comprising the second layer composition are alternately stacked.

[0127] The melt extrusion temperature of the first layer composition may be 220° C. or higher. Specifically, the melt extrusion temperature of the first layer composition may be 230° C. or higher or 240° C. or higher.

[0128] The melt extrusion temperature of the second layer composition may be 180° C. or higher. Specifically, the melt extrusion temperature of the second layer composition may be 190° C. or higher or 200° C. or higher.

[0129] The melt extrusion temperature of the above-mentioned first layer composition and the melt extrusion temperature of the second layer composition may be the same or different. Exemplarily, the difference between the melt extrusion temperature of the first layer composition and the melt extrusion temperature of the second layer composition may be below 20°C or below 15°C. The above-mentioned difference may be above 0°C. For the purpose of adjusting the melt viscosity, there may be a difference in the melting temperature of the first layer composition and the second layer composition. Specifically, when the extruder is constructed in the order of a melt pipe (a pipe for the movement of the molten resin)-a laminating device (e.g., a multi-layer block)-a mold, the temperature of the melt pipe of the first layer composition and the second layer composition may be set to be different. When the melt extrusion process is performed in the above manner, the thickness of each layer in the film can be more easily controlled.

[0130] The stacked body may be formed by alternately stacking the first layer and the second layer into three or more layers. Specifically, the stacked body may be formed by alternately stacking the first layer and the second layer into three to 255 layers.

[0131] The alternately stacked device may be a lamination device suitable for thin film preparation, for example, a feed block, a multi-manifold, etc. may be suitable.

[0132] The above-mentioned step of obtaining an unstretched sheet may include a step of forming the laminated body into a sheet by a process such as bringing the laminated body into close contact with a cooling roll.

[0133] The step of obtaining a packaging film is a step of obtaining a multilayer film by stretching and heat-setting the stacked above sheets.

[0134] The stretching may be biaxial stretching or sequential biaxial stretching. Specifically, the stretching may be 2 to 4 times in the machine direction (MD) at 40 to 130°C and 3 to 6 times in the transverse direction (TD) at 50 to 150°C.

[0135] The heat setting step may be conducted at 50°C to 300°C, 100°C to 200°C, 125°C to 175°C, or 140°C to 160°C.

[0136] Through the above-mentioned stretching and the above-mentioned heat setting, the packaging film can have improved mechanical strength and dimensional stability while having a thin thickness.

[0137] Since the specific description about the packaging film and the said laminated body overlaps with the above description, the description will be omitted.

[0138] The thickness ratio, the number of stacked layers, etc. are the same as those described above, but the thickness of each layer can be controlled and applied by taking into account the stretching process, etc., which will be described below.

[0139] By the above method, a multilayer film with good quality can be prepared in a relatively simple and effective manner. The film prepared in this way can be effectively used as a packaging film.

[0140] Packaging Materials

[0141] A packaging material according to another embodiment includes the packaging film as described above. Since the specific description of the packaging film overlaps with the above description, the detailed description will be omitted.

[0142] For example, the packaging material may be a disposable packaging material, a food packaging material, etc., and may be applied with the above-mentioned packaging film as it is, or may further include an aluminum foil, a color layer, a printing layer, etc.

[0143] Due to the low oxygen permeability of the multilayer film, the above packaging material can effectively prevent the packaged content from being exposed to external oxygen, thereby helping to prevent the deterioration of the contents.

[0144] The following is a more detailed description through specific examples. The following examples are only examples for helping to understand the present embodiment, and the scope of the present embodiment is not limited thereto.

[0145] [Example 1]

[0146] <Preparation of First Layer Composition>

[0147] The first layer composition is prepared by mixing the diol component and the dicarboxylic acid component in an autoclave equipped with a stirrer and a distillation column.

[0148] Specifically, in the first layer composition, the diol component includes 80 mol % of ethylene glycol (EG), 15 mol % of neopentyl glycol (NPG) and 5 mol % of diethylene glycol (DEG), and the dicarboxylic acid component is 100 mol % of dimethyl terephthalate (DMT).

[0149] The first layer composition undergoes an ester exchange reaction with an ester exchange catalyst. Specifically, the catalyst used for the ester exchange reaction is manganese acetate, and the amount of manganese acetate used is 0.07 parts by weight based on the weight of the dicarboxylic acid. Then, the temperature is raised to 220° C. while removing methanol as a by-product to carry out the ester exchange reaction.

[0150] When the above-mentioned ester exchange reaction is completed, silica with an average particle size of 0.28 μm and trimethyl phosphate as a stabilizer are added to the above-mentioned first layer composition, so that the content of the above-mentioned silica is 0.07 weight part relative to 100 weight parts of dicarboxylic acid, and the content of the above-mentioned trimethyl phosphate is 0.4 weight part relative to 100 weight parts of dicarboxylic acid.

[0151] After 5 minutes, 0.035 parts by weight of antimony trioxide and 0.005 parts by weight of tetrabutyl titanate as a polymerization catalyst were added to the above first layer composition and stirred for 10 minutes.

[0152] Next, the first layer composition was transferred to a second reactor equipped with a vacuum device, the temperature was raised to 285° C., the pressure was gradually reduced, and polymerization was performed for about 210 minutes to obtain a first layer composition.

[0153] <Second Layer Composition 1>

[0154] As the second layer composition 1, a butene glycol-vinyl alcohol copolymer (BVOH) prepared by copolymerizing butene glycol and vinyl acetate and then hydrolyzing vinyl acetate can be used.

[0155] Alternatively, as the butene glycol-vinyl alcohol copolymer (BVOH), NICHIGO G-POLYMER, which is a commercially available product sold by Mitsubishi Chemical Corporation, can be used. TM Specifically, NICHIGO GPOLYMER TM The BVE8049P.

[0156] <Second layer composition 2>

[0157] As the second layer composition 2, Soarnol (grade: A4412B, ethylene content: 44 mol%) manufactured by Mitsubishi Chemical Corporation, which is a copolymer of ethylene and vinyl alcohol, was used.

[0158] <Preparation of Multilayer Barrier Film>

[0159] The first layer composition was first dried using a dehumidifying dryer at 100° C. for more than 4 hours, and then secondarily dried at 160° C. for more than 6 hours to remove moisture. The second layer composition 1 was directly applied to the dried packaging.

[0160] Using two extruders and a preset feed block that can be stacked into three layers, the first layer composition was melt-extruded with an extruder at a temperature of 240° C., and the second layer composition 1 was melt-extruded with an extruder at a temperature of 200° C. The discharge ratio (volume ratio) of the first layer composition and the second layer composition 1 was 90:10.

[0161] In the three-layer feed block, the first layer composition was branched into two surface layers, and the second layer composition 1 was branched into an intermediate layer, and then laminated. Thereafter, the laminated body was passed through a 400 mm die and pressed against a cooling roll cooled to 20° C. to obtain a total of three layers of unstretched sheets.

[0162] The three-layer unstretched sheet was stretched 3.0 times in the longitudinal direction at 85°C and 4.0 times in the transverse direction at 110°C, and then heat-set at 150°C with a relaxation rate of 1% to prepare a 20 μm biaxially stretched three-layer film (Example 1).

[0163] [Example 2 to Example 4]

[0164] In Example 2, a film was prepared in the same manner as in Example 1, except that the sheet was made to have a thickness of 45 μm after stretching and heat-setting.

[0165] In Example 3, a film was prepared in the same manner as in Example 1, except that the sheet was made to have a thickness of 60 μm after stretching and heat-setting.

[0166] In Example 4, a film was prepared in the same manner as in Example 1 except that the discharge amount ratio (volume ratio) of the first resin to the second resin was 95:5.

[0167] [Example 5 to Example 8]

[0168] Example 5 prepares a film in the same manner as Example 1, but the difference is that, in the multilayer feed block, the first layer composition is branched into 36 layers, the second layer composition is branched into 36 layers, and then they are alternately stacked, the first layer 11 and the second layer 12 are stacked into 73 layers respectively, the surface layers are located at the outermost layers of the upper and lower surfaces respectively, and the first layer composition is applied to the surface layer so that the composition of the surface layer is the same as that of the first layer 11.

[0169] In Example 6, a film was prepared in the same manner as in Example 5, except that the discharge ratio (volume ratio) of the first layer composition to the second layer composition was 70:30.

[0170] Example 7 prepares a film in the same manner as Example 1, but the difference is that, in the multilayer feed block, the first layer composition is branched into 72 layers, the second layer composition is branched into 72 layers, and then they are alternately stacked, the first layer 11 and the second layer 12 are stacked into 145 layers respectively, the surface layers are located at the outermost layers of the upper and lower surfaces respectively, and the first layer composition is applied to the surface layer so that the composition of the surface layer is the same as that of the first layer 11.

[0171] In Example 8, a film was prepared in the same manner as in Example 7, except that the discharge ratio (volume ratio) of the first layer composition to the second layer composition was 70:30.

[0172] [Example 9 to Example 10]

[0173] In Example 9, a film was prepared in the same manner as in Example 2, except that the second layer composition was ethylene-vinyl alcohol copolymer (EVOH) instead of butene glycol-vinyl alcohol copolymer (BVOH).

[0174] Example 10 prepares a film in the same manner as Example 9, but the difference is that in the multilayer feed block, the first layer composition is branched into 36 layers, the second layer composition is branched into 36 layers, and then they are alternately stacked, the first layer 11 and the second layer 12 are stacked into 73 layers respectively, the surface layers are located at the outermost layers of the upper and lower surfaces respectively, and the first layer composition is applied to the surface layer so that the composition of the surface layer is the same as that of the first layer 11.

[0175] [Comparative Example 1]

[0176] The first layer composition described in Example 1 is used in Comparative Example 1. First, the first layer composition is dried once at 100°C for more than 4 hours using a dehumidifying dryer, and then dried twice at 160°C for more than 6 hours to remove moisture. The first layer composition is melt-extruded using an extruder at a temperature of 240°C. Thereafter, the first layer composition is passed through a 400mm die head and pressed against a cooling roller cooled to 20°C to obtain a single-layer unstretched sheet. The single-layer unstretched sheet obtained as above is stretched 3.0 times longitudinally at 85°C and 4.0 times transversely at 100°C, and then heat-set at a temperature of 150°C at a relaxation rate of 1% to obtain a 45μm biaxially stretched single-layer film (Comparative Example 1).

[0177] [Evaluation Example 1: Oxygen Permeability Evaluation]

[0178] For the multilayer barrier film prepared above, according to ASTM D3985-17, OX-TRAN 702 from MOCON, USA, was used at 50 cm 2 The oxygen permeability is measured under the conditions of test area, 1 atm, 23.0 ± 0.5 °C temperature and 0% relative humidity. [Unit: cc / m 2 ·sky]

[0179] [Evaluation Example 2: Moisture Permeability Evaluation]

[0180] As for the water vapor transmission rate, it was measured according to ASTM F1249-20 using the PERMATRAN-W700 tester of MOCON Company, USA, at a temperature of 37.8±0.5°C and a humidity of 100RH%. [Unit: g / m 2 ·sky]

[0181] [Evaluation Example 3: Film Processability]

[0182] For the multilayer barrier film prepared above with a width of 200 cm, the thickness was measured at intervals of 2 cm, and the maximum thickness (THK max ) and minimum thickness (THK min If the difference between the maximum thickness and the minimum thickness is 3 μm or less, it is judged to be good.

[0183] [Evaluation Example 4: Others]

[0184] The haze of the film was measured using a haze meter NDH-8000N manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with ISO 14782.

[0185] The light transmittance of the film was measured using Ultrascan PRO (manufactured by Hunter Lab, USA) as a spectrophotometer.

[0186] The results of the respective measurements are summarized in Tables 1 and 2 below.

[0187] Table 1

[0188]

[0189]

[0190] Table 2

[0191]

[0192]

[0193] Comparative Example 1 is a film using only the first layer 11. It was confirmed that the film according to Comparative Example 1 had a high oxygen permeability and therefore could not function as a barrier film to block oxygen.

[0194] The films prepared in Examples 1 to 8 had a viscosity of 0.01 cc / (m 2 ·atm·day) and a relatively low oxygen permeability of less than 50g / m 2 Low water vapor transmission rate of less than 1 day. In addition, the films prepared in Examples 1 to 8 according to the present embodiment had good interfacial peeling performance evaluated in the evaluation examples.

[0195] In Example 9 and Example 10, the oxygen permeability is relatively high compared with Examples 1 to 8, but it is sufficient to be used as a packaging film for food, etc., and the moisture permeability is relatively low, showing excellent performance. In addition, the optical properties are also relatively excellent, so it is considered to be suitable for printing, etc. In the case of the interface peeling performance, considering that Examples 9 and Example 10 are the characteristics of samples obtained by coextrusion without applying a separate adhesive layer, it is evaluated that reinforcement such as forming an adhesive layer at the interface is required.

[0196] The preferred embodiments of the present embodiment are described in detail above, but the scope of the present embodiment is not limited thereto. Various deformations and improvements by ordinary technicians in the technical field of the present invention using the basic concepts of the present embodiment defined in the scope of protection of the attached invention claims also fall within the scope of the present embodiment.

Claims

1. A packaging film, characterized in that: comprising a laminate, the laminate comprising a first layer and a second layer disposed on the first layer, The first layer comprises a polyester resin containing a diol residue and a dicarboxylic acid residue, The second layer comprises a vinyl alcohol-based copolymer resin, The packaging film has a viscosity of 10 cc / (m 2 ·day·atm) or less oxygen permeability.

2. The packaging film according to claim 1, characterized in that: The packaging film has a 50g / (m 2 · days) or less.

3. The packaging film according to claim 1, characterized in that: The vinyl alcohol-based copolymer resin is a butene glycol-vinyl alcohol copolymer resin or an ethylene-vinyl alcohol copolymer resin.

4. The packaging film according to claim 1, characterized in that: The thermal decomposition temperature of the vinyl alcohol-based copolymer resin is 210°C to 230°C.

5. The packaging film according to claim 1, characterized in that: The first layer is located on at least one of the outermost layers on both sides of the stacked body.

6. The packaging film according to claim 1, characterized in that: The laminate has a light transmittance of 80% or more in the visible light region with a wavelength of 380 nm to 780 nm.

7. The packaging film according to claim 1, characterized in that: The laminate has a haze of 30% or less.

8. The packaging film according to claim 1, characterized in that: The laminate is formed by alternately stacking the first layer and the second layer in 3 to 225 layers.

9. The packaging film according to claim 1, characterized in that: The maximum thickness deviation (MTD) is expressed by the following formula 2: 200 ) is less than 10 μm: [Formula 2] MTD 200 =THK max -THK min In the above formula 1, THK max It refers to the maximum thickness when the thickness of a packaging film sample with a minimum width of 200 cm is measured every 2 cm. min It refers to the minimum thickness when the thickness of a packaging film sample with a width of 200 cm is measured every 2 cm.

10. A packaging material, characterized in that: The packaging film comprises the packaging film according to claim 1 and is used for packaging food.

Citation Information

Patent Citations

  • Multilayer barrier film

    CA3014699A1

  • Laminate and method for manufacturing laminate

    CN108367562A

  • Heat-sealable film having barrier functionality

    JP2008221811A

  • Gas barrier laminate film

    JP2016020085A

  • BIODEGRADABLE AND COMPOSTABLE FOOD PACKAGING UNIT FROM A MOULDED OR FLUFF PULP MATERIAL WITH A LAMINATED MULTI-LAYER, AND METHOD FOR MANUFACTURING SUCH FOOD PACKAGING UNIT

    NL2022734A